Aesthetic persuasion: how artistic packaging and visual storytelling drive cosmetic brand choices - Muthusamy, Geetha; Hasbullah, Nornajihah Nadia; Naseri, Roszi Naszariah Nasni; Yahya, Wan Kalthom (Faculty of Art and Design, 2025)
In the intensely competitive cosmetics market, brands must transcend mere functionality to engage consumers through sensory and emotional appeal. This study investigates how artistic packaging and visual storytelling serve as mechanisms of aesthetic persuasion that shape cosmetic brand choice, using the Theory of Planned Behavior (TPB) as a conceptual foundation. It is theorized that these aesthetic cues influence attitude, subjective norms, and perceived behavioral control, which in turn affect purchase intention. To empirically validate the proposed framework, this study will employ a quantitative research design involving an online survey of 200 cosmetic consumers. Measurement items will be adapted from established scales in prior literature, ensuring content validity. Data will be analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the hypothesized relationships and assess the model’s predictive power. The findings are expected to provide theoretical contributions by extending TPB to aesthetic persuasion contexts and practical implications for cosmetic marketers aiming to leverage artistic branding strategies to influence consumer choice.